The relationship between corporate governance mechanisms and financial structure decision / Zuria Juhari - Juhari, Zuria (2015)
Corporate governance becomes actively debated over the last decade in analysing the influences on the company's financial decision. Good corporate governance practices possibly will have significant influence in making strategic decisions especially on financial structure of the company, that are taken by board of director. As a result of financial structure decision, there has been an existence of agency conflicts between ownership and management team. Agency theory suggests that there should have a separation of control between principal and agent, so that agent will act on behalf of principal in managing company's resources. Therefore, corporate governance is used as an important tool to mitigate this agency costs. Ordinary Least-squares (OLS) regression is used to investigate the influence of corporate governance variables on company's financial structure decision. The variables of corporate governance mechanisms measures in this thesis are board size, directors' remuneration, CEO duality, tenure of CEO and institutional ownership, while control variable represented by firm size. In addition, financial structure is measured by debt to equity ratio. The main objective of this thesis is to examine the type of financial structure decision among Malaysian companies whereas the second objective is to investigate the relationship between corporate governance mechanisms and financial structure. The results indicate that directors' remuneration has a positive significant relationship with financial structure decision for Malaysian companies. Board size, CEO duality, CEO tenure, and institutional ownership have positively insignificant relationship with the financial structure of the company in Malaysia. Firm size as a control variable used in this thesis has a significant relationship with the financial structure decisions. Overall, most of Malaysian companies prefer to use debt to finance company's operation rather than equity issuance.